United Kingdom : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper on the United Kingdom reviews the IMF's Global Economy Model, which incorporates energy to examine the impact of rising energy prices on the United Kingdom. The model incorporates energy as a final consumption good as well as a primary input in the production process. With energy entering the production process, increases in energy costs affect overall aggregate supply capacity as firms reduce output and factor-utilization rates given the real increase in their cost structures.